Analysis of Maternal Death Related to Eclampsia in a Tertiary Care Centre - Bilkis, Mst Rabeya; Sharmin, Mst Shahana; Sultana, Sobnam; Biswas, Lipika Rani; Ahmed, Kamal Uddin; Zeba, Dilruba; Ara, Iffat (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Eclampsia is an acute and life threatening complication of pregnancy and leading contributor to maternal mortality. This study was aimed to analyze maternal death related to eclampsia in a tertiary care centre. Patients of eclampsia with complications (eclampsia associated with cardiac failure, pulmonary edema, cerebral hemorrhage, renal failure, HELLP syndrome, aspiration pneumonia, disseminated intravascular coagulopathy etc.) were studied and followed up. After detailed history, thorough clinical examination and necessary investigations only the death cases were included for the study. The majority of death occurred in antepartum period (66.33%) and the fetal outcomes were mostly still birth (53.33%), followed by live birth in 43.33% and undelivered in 3.33% patients. Most common etiological factor in eclamptic death was HELLP syndrome (66%) and other causes in decreasing frequency were acute renal failure (26.66%), cerebrovascular accident (33.33%), disseminated intravascular coagulation (23.33%), multiorgan failure (20%), pulmonary edema (16.66%), shock (16.66%) and septicaemia (13.33%). Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(2):74-76.